That time I got reincarnated as a slime. 9 - Fuse (Manga author); Kawakami, Taiki (Kodansha Comics, 2019)
"As players of Monster Hunter and Dungeons & Dragons know, the slime is not exactly the king of the fantasy monsters. So when a 37-year-old Tokyo salaryman dies and wakes up in a world of elves and magic, he's a little disappointed to find he's become a blind, boneless slime monster ... At the suggestion of Demon Lord Carrion, Tempest and Eurazania have sent delegations to each other in the hopes of finding fruitful exchange. Benimaru leads the mission from Tempest, and from Eurazania is a party led by Albis the Golden Serpent. It seems as though trade might begin to flourish, until the members of Eurazania's delegation bristle at Rimuru. Can our gelatinous hero manage to get on their good side and be the glue to form a friendly bond between two nations ...?"--Provided by publisher.